2022
DOI: 10.1007/s40620-022-01390-1
|View full text |Cite
|
Sign up to set email alerts
|

Frailty, appendicular lean mass, osteoporosis and osteosarcopenia in peritoneal dialysis patients

Abstract: Introduction The pattern of chronic kidney disease mineral bone disorder (CKD-MBD) is changing with increasing numbers of elderly patients now treated by dialysis. The risk of falls and bone fractures increases with frailty and sarcopenia. As such we wished to review the association between osteoporosis and frailty and loss of appendicular lean mass (ALM). Methods Dual-energy X-ray absorptiometry (DXA) was used to measure lumbar spine and femoral neck bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
3
0
1
Order By: Relevance
“…This study reported no significant difference between patients on hemodialysis or peritoneal dialysis, but it acknowledged that the small sample size of PD patients may limit this result. One regional multicenter study that included 292 PD patients found that 19% of patients had osteoporosis and 36% had osteopenia [22], somewhat similar to what other studies have demonstrated [23][24][25][26]. In addition, these studies found an increased risk of reduced BMD with lower Body Mass Index (BMI).…”
Section: Introductionsupporting
confidence: 70%
“…This study reported no significant difference between patients on hemodialysis or peritoneal dialysis, but it acknowledged that the small sample size of PD patients may limit this result. One regional multicenter study that included 292 PD patients found that 19% of patients had osteoporosis and 36% had osteopenia [22], somewhat similar to what other studies have demonstrated [23][24][25][26]. In addition, these studies found an increased risk of reduced BMD with lower Body Mass Index (BMI).…”
Section: Introductionsupporting
confidence: 70%
“…Среди хронических заболеваний, следует отметить хроническую болезнью почек (ХБП) тяжёлой степени, где приём белка снижается до 0,2-0,5 г/кг в сутки (при СКФ <30 мл/мин/1,73 м²) для профилактики метаболического ацидоза [35]. К недостатку минеральной плотности костной ткани может приводить дефицит витамина Д и диабетическая болезнь почек [36]. Вероятно, приём витамина Д в профилактических дозировках будет способствовать сохранению костной массы [37].…”
Section: Discussionunclassified
“…As dialysis is now offered to more older patients with advanced CKD, and those with additional co-morbidities in economically advanced countries, then more patients with degrees of frailty are now receiving dialysis [8]. Frail patients tend to be less physically active and have lower muscle mass [9,10] and are greater risk of both sarcopenia and PEW [10].…”
Section: Introductionmentioning
confidence: 99%